Influência da periodontite apical no perfil hematológico de ratos Wistar portadores de aterosclerose: estudo preliminar - Martins, Marina Ottoni [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This study evaluated the influence of apical periodontitis (PA) on the hematological profile of normal or atherosclerosis (AT) rats. Forty male Wistar rats were distributed in 4 groups of 10 animals: control rats (C); rats with apical periodontitis (PA); rats with atherosclerosis (AT); rats with AP and atherosclerosis (PA+AT). Atherosclerosis was induced surgically, by means of an artificial ligation made around the common carotid artery stenosis inner diameter of 0.3mm. One day after surgery, it was administered a dose of vitamin D3 for two days (90,000 IU). The surgically induced animals were fed a hyperlipid diet consisting of a conventional diet associated with 20% lard and 5% sugar throughout the experimental period. After 30 days, the apical periodontitis was induced by exposing the coronary pulp of the first and second upper and lower right molars to the oral medium. After another 30 days, cardiac puncture was performed to remove the hematological tissue, and then the animals were euthanized. Hemoglobin, hemoglobin, hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (CHCM), leukocytes, neutrophils, lymphocytes, monocytes, eosinophils, basophils, platelets, and total plasma protein (PPT). The results obtained were statistically analyzed by Kruskall Wallis and Dunn tests with a significance level of 5% (p <0.05). There was a reduction in the number of leukocytes and basophils in the groups with atherosclerosis (AT and PA+AT), but without significant difference between groups (p <0.05). The PA+AT group had a lower neutrophil value, but no significant difference compared to the other groups (p <0.05). There were fewer monocytes in the groups presenting isolated or associated alterations (PA, AT and PA+AT), when compared to the control group (p <0.05). Eosinophils and Total Plasma Protein significantly reduced in the atherosclerosis groups relative to the control...

O objetivo deste trabalho foi analisar a influência da periodontite apical (PA) no perfil hematológico de ratos normais ou com aterosclerose (AT). Foram utilizados 40 ratos Wistar distribuídos em 4 grupos de 10 animais: C - ratos controle; PA - ratos com periodontite apical; AT - ratos com aterosclerose; PA+AT - ratos com periodontite apical e com aterosclerose. A indução da aterosclerose foi realizada cirurgicamente, por meio de uma amarria em torno da artéria carótida comum com diâmetro interno da estenose de 0,3mm. Um dia depois da cirurgia, foi administrado via oral uma dose de vitamina D3 durante dois dias (90.000 UI). Os animais induzidos cirurgicamente se alimentaram com uma dieta hiperlipídica, composta por ração convencional associada a 20% de banha de porco e 5% de açúcar durante todo o período experimental. Após 30 dias, a periodontite apical foi induzida pela exposição da polpa coronária dos primeiros e segundos molares superiores e inferiores direito ao meio oral. Decorridos mais 30 dias, foi realizada punção cardíaca para remoção do tecido hematológico e em seguida os animais foram eutanasiados. O material coletado foi analisado por meio do hemograma cujos parâmetros analisados foram: hemácias, volume globular (hematócrito), hemoglobina, volume corpuscular médio (VCM), concentração de hemoglobina corpuscular média (CHCM), leucócitos, neutrófilos, linfócitos, monócitos, eosinófilos, basófilos e proteína plasmática total (PPT). Os resultados obtidos foram analisados, do ponto de vista estatístico pelos testes de Kruskall Wallis e Dunn com nível de significância de 5% (p < 0,05). Houve redução no número de leucócitos e basófilos nos grupos com aterosclerose (AT e PA+AT), porém sem diferença significativa entre os grupos (p<0,05). O grupo PA+AT apresentou menor valor de neutrófilos, porém sem...
Keywords: Periodontite periapical; Aterosclerose; Ratos Wistar; Periapical periodontitis